Black box testing on the online quiz application using the Equivalence Partitions method - Huriati, Putri; Azmi, Haryuni; Wati, Yenni; Meidelfi, Dwiny; Lestari, Tri (SOTVI, 2020)
The Quiz Online application is an android-based application that aims to help elementary school children learn and explore the material taught at school, this application can be used anywhere and anytime, parents and teachers can also monitor children's learning progress. To achieve the objectives of this application, it is necessary to test the online quiz application to ensure that the system functions according to user needs. This test is useful to ensure there are no errors that can later cause losses in the future. Testing on the online quiz application using the Equivalence Partitioning method. The steps taken are to make a test design, test limits, test scenarios and expected results. From the results of tests carried out using the Equivalence Partitioning method in the online quiz application, no errors were found and all system functions were running well.